PERGESERAN MAKNA MASKULIN DALAM BUDAYA POPULER (STUDI KASUS KAJIAN SEMIOTIKA IKLAN VT X BTS â€œTIME TO SHINEâ€) - Syafikarani, Aisyi (Visualita Jurnal Online Desain Komunikasi Visual, 2021)
VT Cosmetics comes with new ad that uses BTS's K-Pop star brand ambassador, the ad represents masculinity as an attribute of popular culture. Therefore, this study aims to analyze how the representation of masculinity as an attribute of popular culture in VT x BTS "Time to Shine" advertisements. This research is included in qualitative research by searching data through literature and documentation studies. Then the data that has been obtained were analyzed using Roland Barthes' semiotic theory. The results of this study indicate that masculine men are not always represented only through the form of a manly, strong, and courageous body like the current convention. However, it also becomes natural when a man also pays attention to the beauty and health of his skin like a woman, this is a result of the development of Hallyu culture, which is pop culture. In the end, new masculinity is formed as an attribute of popular culture, its presence is favored by a certain group of people, so that it is very likely to develop in the future. The results of this study are useful for practitioners and academics engaged in advertising.